Technical Vocational Education and Training (TVET) Capability Approach Framework [TVET-CAF] - Mohd Nordin, Rumaizah (Online Journal for TVET Practitioners, 2022)
TVET played an important role as one of supply mechanism on the competence human capital towards the economic growth of Malaysia including for construction industry. However, the mass of unemployed graduates has caused their readiness towards involvement in the industry become questionable. Thus, the aim of the study is to propose a TVET-CAF framework to enhance the career readiness of Construction Technology graduates through reviews of literature. The major elements of the framework are: the relevance of the graduates, efficacy level of the graduates and ways to enhance level of efficacy the graduates. Therefore, it will assist in improving the quality of education for the graduate towards better student outcome alongside with RMK-11 strategic thrust which is accelerating human capital development for an advanced nation.